Report the Second ASEAN Academic Conference on Disaster Health Management 2023 - ASEAN Journal of Disaster Health Management (ASEAN Journal of Disaster Health Management (AJDHM), 2025)
This report outlines the key outcomes of the 2nd ASEAN Academic Conference (AAC), which gathered academics and professionals from across the region to exchange insights and foster collaboration. The conference featured keynote speeches, research presentations, and panel discussions addressing regional challenges. Contributions from ASEAN countries highlighted diverse perspectives and actionable recommendations, reinforcing academic partnerships and paving the way for the 3rd AAC.